Tanggung Jawab Profesional dalam Keamanan Cyber Perspektif Etika dan Hukum - Amiruddin Amiruddin; Mohd Wildan Qasthari; Muhammad Nazar; Nov Indra Adiwira Suryantyo; Rahmadani Rahmadani; Raja Rahmad Hafizhul Manik; M. Fadil Nasution (Jurnal Kridatama Sains dan Teknologi, 2026)
Cybersecurity is an essential aspect of protecting data and digital infrastructure in the era of rapid technological transformation. The increasing number of cyber threats requires professional responsibility that goes beyond technical aspects and considers ethical and legal dimensions. This study aims to examine professional responsibility in cybersecurity from ethical and legal perspectives and to analyze the challenges in its implementation. This research employs a qualitative approach using literature review and case study methods. Data were collected through the analysis of scientific journals, cybersecurity regulations, and organizational policies, as well as semi-structured interviews with cybersecurity professionals, including system administrators, information security analysts, and IT security practitioners. Data analysis used thematic analysis to identify patterns of professional responsibility in cybersecurity practices. The findings indicate that professional responsibility in cybersecurity includes the protection of personal data, compliance with regulations such as the General Data Protection Regulation (GDPR) and the California Consumer Privacy Act (CCPA), and the implementation of professional codes of ethics such as the ISC² Code of Ethics and the EC-Council Code of Ethics. In addition, the study reveals that the main challenges lie in ethical hacking practices, user activity monitoring, and vulnerability management, which create dilemmas between security, privacy, and legal compliance. This study concludes that integrating ethics, law, and organizational policies is essential to creating a secure and responsible cybersecurity ecosystem. Professional codes of ethics play a crucial role in guiding ethical behavior and maintaining integrity in facing increasingly complex cyber threats